Thermal stability of starch bionanocomposites films: Exploring the role of esterified cellulose nanofibers isolated from crop residue. (1st March 2021) - Ahuja, Dheeraj; Kumar, Lokesh; Kaushik, Anupama
Graphical abstract: Highlights: CNFs obtained from wheat straw, a crop-residue were esterified for better dispersion. GPS nanocomposites were prepared with esterified CNFs (m-CNFs) and pristine CNFs. Morphology, water vapour permeability (WVR) and thermal stability were studied. m-CNFs were better than pristine CNFs for WVR reduction and thermal stability. WVR reduced by 80 % and activation energy of thermal degradation improved by 52 %. Abstract: Thermal stability and degradation kinetics were studied for glycerol plasticized starch (GPS) nanocomposites reinforced with cellulose nanofibers (CNFs) extracted from wheat straw, a crop residue. To assess the effect of surface modifications on CNFs in improving thermal degradation behavior, three types of CNFs were used viz pristine (p-CNFs), esterified (m-CNFs) and a mixture of pristine and esterified (x-CNFs) in equal ratio. Three kinetics models Ozawa-Flynn, Freidman and Kissinger's were used to evaluate activation energy of thermal degradation for pristine and nanocomposite samples. Properties like morphology, crystallinity and water vapor permeability (WVP) were also evaluated. Morphology of m-CNF/GPS bionanocomposites films was superior as compared to other films with better interfacial bonding. Moreover, m-CNFs also exhibited 81 % reduction WVP as compared to pristine GPS films. Activation energy revealed significant enhancement i.e. as high as 52 % in thermal stability with addition of CNFs. Consequent relation between morphology and thermal stability was also established.